Sloping landscape - Ifengspace (Singapore : Basheer Graphic Books, 2014)
'Sloping terrain is commonly around us with sloping landscape design being used widely in various conditions and surroundings. Sloping landscape can be applied in an urban square being built on a slope, paths being paved in a park which contains rugged topography, a resort at the foot of a hill, a residence or a garden appearing on the mountainside, etc. This book presents the latest and most creative sloping landscape design around the world.' --Back cover.
Keywords: Landscape design; Landscape architecture